Mengungkap Kedalaman Makna dengan Metafora: Studi Analisis Puisi oleh Pengarang - Naufal Daffa Adibta; Geraldy Calvin; Aditama Surya Permana (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2024)
This research aims to describe the use of metaphor in poetry as a means of expressing the depth of the author's meaning and expression. Metaphors are often used to enrich poetic language by connecting complex concepts figuratively. Qualitative analysis methods are used to examine how metaphors are used to communicate emotional and intellectual messages in poetry, with a focus on the author as a conveyer of meaning. The findings suggest that metaphor can serve as a powerful tool for expressing complex and deep ideas in poetry, enriching the reading experience and literary interpretation.